Implementing interactive courseware into EFL business writing: computational assessment and learning satisfaction. Issue 1 (2nd January 2019) - Tsai, Shu-Chiao
ABSTRACT: The implementation of interactive courseware within a task-based learning (TBL) approach was conducted for English Writing for Business to Chinese students in an applied foreign languages department housed in a university of technology. The development of the interactive courseware is based on Mayer's multimedia learning theory, which allows learners to construct verbal and visual cognitive representations and integrate them; its language learning focus is keyed to Chapelle's suggested criteria for development of multimedia CALL (computer assisted language learning). According to the curriculum, students had to accomplish three tasks rooted in the real world workplace: inquiry, negotiation, and complaint. Evaluation of the interactive ESP courseware into TBL instruction was based upon data from students' pre- and post-writing performance measured by three different types of online computational assessments. In addition, a questionnaire survey about learning satisfaction was administered. The results indicate that students had significantly better post-writing performance and showed greater satisfaction after self-studying with the courseware-implemented instruction, which effectively integrated content knowledge, integrative English skills and writing practices embedded in the courseware. This instruction could be a potentially useful for teaching business writing by providing both content knowledge and its related integrative language practice.